INFLUENCE OF VARIETY FEATURES AND FERTILIZERS ON GRAIN PRODUCTIVITY OF SPRING TRITICALE - Ishchenko , V.A. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
By the experimental studies have established the peculiarities of formation the productive stems, crop yields and grain quality of domestic varieties of spring triticale when growing them on two fertilization backgrounds. Providing the spring triticale crops with mineral nutrients is a necessary condition for improving the grain productivity of new varieties when grown in the Steppe zone. Higher crop yields of 3,77 and 3,48 t/ha of spring triticale on the natural background were formed by varieties Hlibodar Kharkivs’kyí and Boryviter, on the background of N30P30K30 – 4,72; 4,58 and 4,57 t/ha varieties Hlibodar Kharkivs’kyí, Legin’ Kharkivs’kyí and Sontsedar Kharkivs’kyí. The crop yield of triticale depended on the conditions of moisture supplying during the formation of vegetative organs and the formation of elements of individual plant productivity and the influence percentage of the nutrient background was 57,2–78,0 %, varietal characteristics – 7,8-21,1 %. The content of protein and gluten in triticale grain depended on both weather conditions and varietal characteristics. The content of protein and gluten in triticale was 9,7–11,8 % and 14,2–17,1 % (without fertilizers), N30P30K30 – 10,4–12,2 % and 14,9–17.3 %, respectively. Higher protein content on both fertilization backgrounds was provided by the variety Volia, and gluten by Dar Khliba.